Religious Attitudes and Home Bias - Carlo Reggiani; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
Home bias affects trade in goods, services and financial assets. It is mostly generated by "natural" trade barriers. Among these dividers we may list many behavioral and sociological factors, such as status quo biases and a few kind of 'embeddedness'. Unfortunately these factors are difficult to measure. An important part of 'embeddedness' may be related to religious attitudes. Is there any relation between economic home bias and religious attitudes at the individual tier? Our aim is to provide a first answer to this question, by going through the econometric analysis of data from a survey conducted among in 11 European universities.
Keywords: 330